Burial customs, the afterlife and the pollution of death in ancient Greece - Francois P. Retief; Louise Cilliers (Acta Theologica)
Funerary practices in ancient Greece were influenced by contemporary views on the afterlife and by concepts of pollution, but also by a desire to limit costs and a need to prevent the process of burial from causing inconvenience to the community or providing an opportunity for exploitation by those with ulterior motives. Plato (Hippias Maior 291d and e) defined the ideal of any Greek as to be rich, healthy and honoured; to live to a grand old age; to bury his parents with honour, and ultimately to be buried in turn by his own children with due respect. This study investigates the views on disposing of the dead which were prevalent from the 8th to the 4th century BC in Greece, and in Attica in particular. The sources consulted include Homer's epic poems, archaeological data and vase paintings, as well as the writings of later historians, philosophers and other prominent people.